KESADARAN DIRI MENURUT TUTUR JATISWARA: MERAJUT KEMBALI KERUKUNAN HIDUP UMAT BERAGAMA - I Komang Suastika Arimbawa; Made G. Juniartha; I Gede Dedi Diana Putra (STAH Dharma Sentana Sulawesi Tengah, 2020)
Religious friction begins to take shape. Many cases of intolerance have occurred around us, both those arising from differences in religion and differences in beliefs, both external and internal religions. All of these cases are a big challenge for diversity and humanity. Cooperation from all components is needed to encourage awareness of each individual to respect each other, love each other, and respect each other so that they can live side by side in harmony. The